Perceived Personal Risk of Victimization as Predictors of Place Attachment in Festac Housing Estate, Lagos, Nigeria - Okunola, Olusegun Olanrewaju; Ogunbodede, Bolawole; Solaja, Ayoola; Jobi, Akinfolarin (International Journal of Built Environment and Scientific Research, 2025)
Scholars have observed that residents who perceive their neighbourhoods as unsafe may become eventually distant, reducing their sense of attachment, community participation and pride in their surroundings. This study examines how perceived personal risk of victimization can impact place attachment in an urban residential area. The study uses quantitative survey method to investigate the relationship. The findings indicate that the most rated element of place attachment is place identity in both types of housing. There is also no significant difference in perceived personal risk of victimization and place attachment in both single and multiple family house types. The findings also indicated that perceived personal risk of victimization is a significant predictor of place attachment in single family neighbourhoods but not in multiple family neighbourhoods. Nonetheless perceived personal risk of victimization is a significant predictor of place attachment in the entire study area.